Language Impairment and Right Hemiparesis in a 54-Year-Old Woman - Biller, Jose; Venizelos, Alexander (Frontiers in Neurology, 2011)
A 54 year-old woman presented to the emergency room with 3 months of slurred speech, language problems, and right hemiparesis. Initial impression based on history, exam and imaging was brain abscess versus primary or metastatic neoplasm. Brain biopsy of the lesion and pathologic specimens were obtained. Below is a description of her presentation, hospital course, imaging, and pathology, as well as a short discussion of the final diagnosis.